Visualizing dynamics using 100 kHz 2D IR spectroscopy and microscopy - Tracy, Kathryn Marie, author; Krummel, Amber T., advisor; Levinger, Nancy E., committee member; Szamel, Grzegorz, committee member; Krueger, David A., committee member; Fisk, John D., committee member (Colorado State University. Libraries, 2018)
2D IR spectroscopy is a nonlinear optical method with the ability to characterize condensed phase chemical systems. It offers information regarding structure and dynamics of chemical systems. Recent efforts have been made to resolve spatially the molecular structure and dynamics of heterogeneous samples, which shows the feasibility of ultrafast 2D IR microscopy. To image more efficiently, we have moved away from the Ti:sapphire based laser systems and OPA systems that operate at one to several kHz typically used in 2D IR spectroscopy. Instead, for the first time we have demonstrated higher repetition rate, 2D IR spectroscopy at 100 kHz. Achieving this higher repetition rate was accomplished by utilizing advances in diode pumped ytterbium oscillators and amplifiers, and is based on an OPCPA utilizing Mg:PPLN followed by DFG in ZGP. Using this system, we have for the first time, demonstrated the interfacing of IR compatible microfluidics with 2D IR spectroscopy to examine the solvatochromic pseudo-halide anion, cyanate in cosolvent environments. This high repetition rate source also provided a path to 2D IR microscopy experiments that explore the dynamics of complex, heterogeneous, chemical systems. We have shown the chemical dynamics in a room temperature ionic liquid microdroplet. Spatially resolved time-dependent 2D IR signals reveal three regions with different chemical dynamics—the bulk, the interface, and a region between the bulk and interface. This demonstration provides proof-of-concept to use 2D IR microscopy on a wide array of additional chemical systems.
Keywords: ultrafast dynamics; ultrafast spectroscopy; OPCPA; 2D IR microscopy; ultrafast lasers; 2D IR spectroscopy